2015
DOI: 10.1021/acs.macromol.5b01528
|View full text |Cite
|
Sign up to set email alerts
|

Deeper Insight into the MADIX Polymerization of Vinylidene Fluoride

Abstract: Controlled radical polymerization protocols for vinylidene fluoride (VDF) are still very elusive. MADIX polymerization of VDF has very rarely been reported. The synthesis of PVDF using MADIX solution polymerization was thus investigated in detail. More efficient protocols for solution polymerization were developed and afforded relatively well-defined PVDF. Careful polymer chain-end monitoring using MALDI-TOF as well as 1H, 19F, and HETCOR 1H–19F NMR revealed that VDF reverse additions and transfer to solvent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
161
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(178 citation statements)
references
References 44 publications
(54 reference statements)
11
161
0
1
Order By: Relevance
“…In particular, this is because MADIX can control the polymerization of so‐called less‐activated monomers (LAM) such as vinyl acetate (VAc), N ‐vinylpyrrolidone (NVP), and N ‐vinylcarbazole. The use of MADIX polymerization has also been reported for the homo‐ and copolymerization of fluoromonomers such as vinylidene fluoride . MADIX polymerization has been applied for the preparation of polymer brushes .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, this is because MADIX can control the polymerization of so‐called less‐activated monomers (LAM) such as vinyl acetate (VAc), N ‐vinylpyrrolidone (NVP), and N ‐vinylcarbazole. The use of MADIX polymerization has also been reported for the homo‐ and copolymerization of fluoromonomers such as vinylidene fluoride . MADIX polymerization has been applied for the preparation of polymer brushes .…”
Section: Introductionmentioning
confidence: 99%
“…CTAs for RAFT polymerizations of ethylene used in our earlier work [13] (4,5)and in the present one (4, 6-12). CTAs for RAFT polymerizations of ethylene used in our earlier work [13] (4,5)and in the present one (4, 6-12).…”
Section: Resultsmentioning
confidence: 84%
“…Reversible deactivation radical polymerization (RDRP) [1] is am ature technology that has been extensively studied for almost twenty-five years. [2,3] Thev ast majority of monomers polymerizable via ac onventional free radical mechanism have been successfully used in RDRP,leading to amyriad of new polymer architectures and properties.H owever,t he RDRP of some monomers,i ncluding several monomers of major industrial importance, [4][5][6] remains challenging.E thylene,w hich leads to polyethylene (PE), the most-produced polymer worldwide,i so ne such monomer.E thylene is gaseous under ambient conditions and requires specific expertise for its polymerization in autoclaves.W ith ac ritical point at 50.4 bar and 9.2 8 8C, ethylene becomes asupercritical fluid above these conditions.P olymerization therefore takes place in amore complex medium than for most conventional liquid monomers. [7] Furthermore,p ropagating polyethylenyl radicals (PEC)a re very reactive.G enerating this reactive species through homolytic bond cleavage is difficult, which rules out RDRP techniques based on reversible termination (for example,n itroxide-mediated polymerization [8] or atomtransfer radical polymerization [9,10] ).…”
Section: Introductionmentioning
confidence: 99%
“…But, for fluoropolymers, the situation appears reversed since ITP of fluoroalkenes already led to commercially available TPEs as soon as 1984 (Daiel® commercialized by the Daikin company (Scheme ), [34] followed by Viton® and Tecnoflon®, marketed by Dupont (now Chemours) and Solvay Solexis (now Solvay Specialty Polymers), respectively. Overviews on RDRP of fluorinated monomers were reported via ITP or from techniques involving either borinates or xanthates (named RAFT/MADIX technology) …”
Section: Applicationsmentioning
confidence: 99%
“…In 2015, a comprehensive study of RAFT polymerization of VDF was reported . The resulting PVDF‐xanthate led to a wide range of architectures (Scheme ) including block (that could self‐assemble into micelles in water), graft, dendrimers, and 4‐arm star copolymers…”
Section: Applicationsmentioning
confidence: 99%